The pastor and the parish pastoral council - Adamczyk, Jerzy; Mazur, Karolina (Prawo Kanoniczne, 2024)
The subject of this article is the problem of the relationship between the pastor and the parish pastoral council. The aim of the study was to show and clarify, on the basis of certain regulations, the rights and duties of the pastor in relation to the council as a recommended consultative structure in the Church. This research objective was realized by means of a description and a thorough analysis of the current regulations and texts of the ecclesiastical magisterium. The analysis of the aforementioned sources allowed several main conclusions to be drawn. Firstly, it was pointed out that the parish pastoral council is a desirable consultative institution, which is an expression of the active participation of the faithful in the realization of the Church's mission in the world. Secondly, the position of the pastor as chairman of the council is shown. Thirdly, an important practical issue concerning the possibility of the pastor to dissolve the council and the conditions for this act has been clarified and justified.